Corner of Professors Row and Packard Avenue Homes of Professors Shipman (now Zeta Psi), Fay, and Bray (now Delta Tau Delta), n.d. - Unknown (Tufts Archival Research Center, 2005)
10 x 8 (Baseball game on what is now President's Lawn)